2014
DOI: 10.1128/jcm.01798-13
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification and Subtyping of Helicobacter cinaedi Strains by Intact-Cell Mass Spectrometry Profiling with the Use of Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry

Abstract: Helicobacter cinaedi infection is recognized as an increasingly important emerging disease in humans. Although H. cinaedi-like strains have been isolated from a variety of animals, it is difficult to identify particular isolates due to their unusual phenotypic profiles and the limited number of biochemical tests for detecting helicobacters. Moreover, analyses of the 16S rRNA gene sequences are also limited due to the high levels of similarity among closely related helicobacters. This study was conducted to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…H. cinaedi is not included in the FDA-cleared Bruker Biotyper or Vitek MS (bioMérieux) databases as of the time of writing this article, although we identified the isolate to the species level (score of Ͼ2.0) with the Bruker Biotyper RUO database. In addition, Taniguchi et al showed that it is possible to use individual MALDI-TOF profiles to both identify and subtype H. cinaedi (5).…”
Section: Discussionmentioning
confidence: 99%
“…H. cinaedi is not included in the FDA-cleared Bruker Biotyper or Vitek MS (bioMérieux) databases as of the time of writing this article, although we identified the isolate to the species level (score of Ͼ2.0) with the Bruker Biotyper RUO database. In addition, Taniguchi et al showed that it is possible to use individual MALDI-TOF profiles to both identify and subtype H. cinaedi (5).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a human clinical strain, H. cinaedi N73 strain, that forms single colonies on agar plates was used in this study. The N73 strain had been isolated from human blood cultures during routine diagnosis of bacteremia in a patient admitted to the University of Miyazaki Hospital . It was grown on Brucella agar (Becton Dickinson, BD Biosciences, Tokyo, Japan) containing 5% defibrinated horse blood (Nippon Biotest Laboratories, Tokyo, Japan) at 37°C for 2–3 days under microaerobic conditions (75% N 2 , 10% CO 2 , 5% H 2 and 10% O 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Vandamme et al also described one isolate from dog faeces (LMG 16312) that was not confidently identified as H. cinaedi by its phenotype [40]. A similar discrepancy between human and animal isolates has been recently recognized using a matrix-assisted laser desorption/ionization time-of-flight mass spectrometry system [36].…”
Section: Introductionmentioning
confidence: 96%